MODERASI NON PERFORMING FINANCING (NPF) PADA PENGARUH PROFIT SHARING RATIO (PSR) DAN ZAKAT PERFORMANCE RATIO (ZPR) TERHADAP RETURN ON ASSET PADA BANK UMUM SYARIAH - Puja Hairani Siregar; Husnul Khotimah (Universitas Veteran Bangun Nusantara, 2025)
In Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the period 2019–2023, this study examines the impact of Profit Sharing Ratio (PSR) and Zakat Performance Ratio (ZPR) on Return on Assets (ROA) by using Non-Performing Financing (NPF) as a moderation variable. The data used were in the form of secondary data obtained from the annual financial statements of ten Islamic commercial banks for five years of observation and analyzed using a quantitative approach through moderation regression analysis. The results of the study showed that PSR had a positive and significant effect on ROA, both before and after being moderated by NPF. In contrast, ZPR did not show a significant influence on ROA, either with or without the role of the moderation variable. In addition, NPF was not shown to moderate the relationship between PSR and ZPR to ROA, and the SIZE control variable also did not have a significant effect. These findings affirm the importance of optimizing profit-sharing-based financing and more strategic zakat management to improve the financial performance and sustainability of Islamic commercial banks.